His Holiness the Dalai Lama : - Strober, Deborah H. (John Wiley & Sons, 2005)
This biography presents a fascinating mosaic of His Holiness the Dalai Lama as a multifaceted individual, viewed from the perspectives of a wide range of people who have encountered him over the past seventy years. The picture that emerges is the epitome of a sublimely balanced human being: with open-minded intelligence and unconditional compassion, an eagerness to engage with the world and a love of solitary meditation, embodying qualities of nobility and humility, of mature authority and childlike humor and playfulness. He is a complex man - a statesman and a holy man - who thinks of himself as a simple Buddhist monk. He inspires us all to become better people and to treat each other with love and respect, as he does with everyone he meets